ANALISIS PENGARUH VARIASI GRADE BIOETANOL TERHADAP DISTRIBUSI TEMPERATUR NYALA API DAN UNJUK KERJA PADA KOMPOR BIOETANOL TANPA SUMBU TIPE TOP BURNER - Adhitia Yanuar Pratama; Andi Sanata; Hary Sutjahjono (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2013)
Top burner cotton less bioethanol stove is one of the appliances that apply the use of renewable fuels for domestic capacity. Application of this stove burner is a solution for scarcity of fossil fuel supplies. This study focused on variations in the distribution of flame temperature and performance on the top burner as grade of bioethanol varies at value of 55%, 70%, 85%, and 97%. Flame temperature distribution measured at of their hot spots and then simulated using Matlab R2011a to obtain isothermal contour flame shape and determine the flame temperature distribution of the flame. Performance testing used Standard International Water Boiling Test version 4.1.2 to determine the power, thermal efficiency, specific fuel consumption, and heat transfer. Results obtained that the flame temperature distribution, in the form of profiles and contours isothermal flame, reached its optimum when using bioethanol grade of 97%. Optimal performance on a stove burner using bioethanol 97% with power stove equal to 1.85 kW, the thermal efficiency of 72.21%, specific fuel consumption (Sfc) 0.512 kgbb/kguap, and heat transfer at value of 2,959 kW was also achieved at the same grade. The higher grade bioethanol used to increase the flame temperature distribution and performance of the stove. Keywords: Bioethanol, Stove, Temperature Distribution, Performance